Epstein‐Barr virus and risk of non‐Hodgkin lymphoma in the cancer prevention study‐II and a meta‐analysis of serologic studies. Issue 1 (5th June 2014) - Teras, Lauren R.; Rollison, Dana E.; Pawlita, Michael; Michel, Angelika; Brozy, Johannes; de Sanjose, Silvia; Blase, Jennifer L.; Gapstur, Susan M.
<x xml:space="preserve">Abstract</x> Epstein‐Barr virus (EBV) causes rare, malignant lymphomas. The role of EBV in other non‐Hodgkin lymphomas (NHLs) remains unclear, but mildly reduced immune function could lead to reactivation of EBV and subsequent NHL. We examined the association between prospectively‐collected plasma EBV antibodies and NHL risk in the Cancer Prevention Study‐II (CPS‐II) Nutrition Cohort and conducted a meta‐analysis of our and published results. The CPS‐II study included 225 NHL cases and 2:1 matched controls. No associations were observed between EBV serostatus or antibody levels and risk of NHL overall. However, when including only the three most common types of NHL (diffuse large B‐cell lymphoma, follicular lymphoma, chronic lymphocytic leukemia/small lymphocytic lymphoma), high compared to low early antigen (EA‐D) diffuse and BZLF1‐encoded replication activator antibodies were associated with approximately 60% higher risk of NHL. Odds ratios (ORs) for EBV nuclear antigen‐1 and viral capsid antigen (VCA)‐p18 were elevated but not statistically significant. In the meta‐analysis, both EA (summary OR = 1.52, 95% confidence interval (CI): 1.16–2.00) and VCA (summary OR = 1.20, 95% CI: 1.00–1.44) were positively associated with NHL risk. These results suggest EBV may be associated with a wider spectrum of NHL subtypes, but further study is needed to confirm and fully understand these associations.